The human decatenation checkpoint - Deming, Paula B. (The National Academy of Sciences, 2001)
Chromatid catenation is actively monitored in human cells, with progression from G(2) to mitosis being inhibited when chromatids are insufficiently decatenated. Mitotic delay was quantified in normal and checkpoint-deficient human cells during treatment with ICRF-193, a topoisomerase II catalytic inhibitor that prevents chromatid decatenation without producing topoisomerase-associated DNA strand breaks. Ataxia telangiectasia (A-T) cells, defective in DNA damage checkpoints, showed normal mitotic delay when treated with ICRF-193. The mitotic delay in response to ICRF-193 was ablated in human fibroblasts expressing an ataxia telangiectasia mutated- and rad3-related (ATR) kinase-inactive ATR allele (ATR(ki)). BRCA1-mutant HCC1937 cells also displayed a defect in ICRF-193-induced mitotic delay, which was corrected by expression of wild-type BRCA1. Phosphorylations of hCds1 or Chk1 and inhibition of Cdk1 kinase activity, which are elements of checkpoints associated with DNA damage or replication, did not occur during ICRF-193-induced mitotic delay. Over-expression of cyclin B1 containing a dominant nuclear localization signal, and inhibition of Crm1-mediated nuclear export, reversed ICRF-193-induced mitotic delay. In combination, these results imply that ATR and BRCA1 enforce the decatenation G(2) checkpoint, which may act to exclude cyclin B1/Cdk1 complexes from the nucleus. Moreover, induction of ATR(ki) produced a 10-fold increase in chromosomal aberrations, further emphasizing the vital role for ATR in genetic stability.